PERSEPSI MAHASISWA EKONOMI TERHADAP IMAGE AKUNTANSI (STUDI KASUS PADA UNIVERSITAS DIPONEGORO SEMARANG) - Hani Werdi Apriyani (Jurnal Akuntansi Indonesia, 2016)
The purpose of this study is to determine, whether in the presence of Accounting profesion education or PPA (Pendidikan Profesi Akuntansi) will change the student perception to the image of accounting which determinestudent choice to major in accounting. This study uses the cognitive theory of planned behavior as the framework to investigate the factor that limit student interest to the field of accounting. The main findings are, that the student perception of the benefit of PPA is positively related to student’s choice tomajor in accounting, wether non accounting student perceived that they tend to choose non accounting major because non other accounting major is not boring. Hipotesis 2 is rejected, it can be inferred that non accounting student’s perception of the image of accounting in the presence PPA is related to their decision to choose non accounting major.